Application of Fuzzy Multi Criteria Decision Making (FMCDM) and TOPSIS in Selecting Prospective Employees - Lailatul Badria; Sriani (Academic Bright Collaboration, 2026)
Purpose – The primary objective of this research is to design and build a web-based Decision Support System (DSS) to evaluate and hire prospective candidates at Perumda Tirtanadi. To achieve this, a hybrid methodology combining Fuzzy Multi-Criteria Decision Making (FMCDM) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) is implemented. The proposed system is intended to reduce subjectivity and improve the effectiveness of the employee selection process. Methods – In this framework, FMCDM is utilized to translate subjective, linguistic evaluations into precise crisp values through a defuzzification process, which subsequently establishes the relative weights of the evaluation criteria. Afterward, these weights are integrated into the TOPSIS algorithm to calculate the final rankings of the applicants across nine specific benchmarks, namely GPA, Basic Competency Test (TKD), psychological test score, attitude, communication skills, work experience, politeness, field expertise, and personal development plan. The system was implemented as a web-based application using PHP and MySQL. Findings – The developed system successfully performed automatic FMCDM weighting and TOPSIS ranking. The ranking results were consistent with manual calculations, indicating that the proposed approach was correctly implemented and capable of producing accurate candidate rankings. Research implications – This study used recruitment data from a single organization, namely Perumda Tirtanadi Medan. Consequently, the applicability of the outcomes is restricted to the specific criteria and administrative environment of this particular utility company and may not be directly generalizable to other organizations. Originality – This study integrates FMCDM for criteria weighting and TOPSIS for candidate ranking into a web-based decision support system, providing a practical and objective approach to employee selection at Perumda Tirtanadi.